Peran Blended Librarian dalam Pelaksanaan User Education Berbasis Daring di Perpustakaan IAIN Kudus - Radiya Wira Buwana (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
During the COVID-19 pandemic, user education activities at the IAIN Kudus Library were held online. This activity is a form of adaptation carried out by the IAIN Kudus Library to continue to be able to work effectively and efficiently in serving users during the pandemic. As an activity that is fully online, it requires a very complex role from the librarian so that it can be carried out optimally. This study aims to discuss how the librarian of the IAIN Kudus Library implements the role of the blended librarian in the implementation of the user education activities. This research was conducted with a descriptive qualitative research method. The data collection method used in this research is through the observation method combined with the literature study method. The results of this study indicate that online-based user education activities at the IAIN Kudus Library can run smoothly because librarians at the IAIN Kudus Library can apply the role of blended librarians in carrying out these activities. The forms of blended librarian's roles include academic librarian, IT librarian, communicative librarian, teaching librarian, and manager.